Answer:
(1-x2)× (2-3x)2
(1-x2) ×(8-36x+54x2-27x3)
8-36x+54x2-27x3-8x2+36x3-54x4+27x5
8-36x+46x2+9x3-54x4+27x5
Answer: 27x5-54x4+9x3+46x2-36x+8
Step-by-step explanation:
step 1- expand the expression
step 2- remove the parentheses
step 3- collect like terms
step 4- reorder the terms
Answer:
153.94
Step-by-step explanation:
about this amount
The old mean was 51 now the mean is 42.33... (round that to 42) 51 - 42 = 9
Answer:
k = 6
Step-by-step explanation:
im guessing you meant solve for k
0.17k - 0.43 = 0.25k + 0.05
-0.17k -0.17k
-0.43 = 0.08k + 0.05
-0.05 -0.05
-0.48 = 0.08k
divide both sides of the equal sign by 0.08
6 = k